1977
DOI: 10.4319/lo.1977.22.2.0181
|View full text |Cite
|
Sign up to set email alerts
|

A new method for physical limnology—tritium‐helium‐3 ages—results for Lakes Erie, Huron, and Ontario1

Abstract: A new method in physical limnology based on the radioactive tracer tritium and its stable daughter product, 'He, is examined. The 3He produced by the in situ decay of tritium can be used to calculate an effective water mass age. These ages can then be used to estimate gas exchange rates, gas renewal epilimnion.Physical mixing mechanisms in lakes have been qualitatively explained for many years. However, the quantitative treatments lag considerably due to lack of adequate methods. While a nomograph for determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
56
0

Year Published

1983
1983
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(56 citation statements)
references
References 12 publications
0
56
0
Order By: Relevance
“…In limnology, the application of 3 H-3 He dating (Torgersen et al 1977(Torgersen et al , 1981Aeschbach-Hertig et al 1996;Hohmann et al 1998) and dating by CFC-11 and CFC-12 (Weiss et al 1991;Weiss and Volmer 1999;Peeters et al 2000a;Aeschbach-Hertig et al in press) is well established. The use of a combination of these tracers improves the reliability of the interpretation of the tracer concentrations in terms of mixing and deep-water residence times (Peeters et al 1997(Peeters et al , 2000a.…”
mentioning
confidence: 99%
“…In limnology, the application of 3 H-3 He dating (Torgersen et al 1977(Torgersen et al , 1981Aeschbach-Hertig et al 1996;Hohmann et al 1998) and dating by CFC-11 and CFC-12 (Weiss et al 1991;Weiss and Volmer 1999;Peeters et al 2000a;Aeschbach-Hertig et al in press) is well established. The use of a combination of these tracers improves the reliability of the interpretation of the tracer concentrations in terms of mixing and deep-water residence times (Peeters et al 1997(Peeters et al , 2000a.…”
mentioning
confidence: 99%
“…On the basis of a thorough theoretical analysis of stability and neutrally buoyant transport in lakes [Peeters et al, 1996] and on a detailed set of conductivity-temperature-depth (CTD) data the authors showed (1) that the Selenga River is important for deep water renewal in the central basin and most likely also in the southern basin, and (2) that deep water renewal in the northern basin is brought about mainly by a combination of small salinity and temperature gradients between the central and northern basins. Torgersen et al [1977] were the first to apply this method to limnic systems, using it to estimate gas exchange rates, gas renewal at ramover, and vertical diffusivity in the epilimnion in Lakes Erie, Huron, and Ontario.…”
mentioning
confidence: 99%
“…The data at 115 m and 125 m, however, have not yet been adequately explained. Mid-depth maximum in 8 3 He and t are not unusual and were found by Torgersen et al (1977) in Lake Ontario. They are seen to be the result of incomplete mixing in the last phases of turnover.…”
Section: Discussionmentioning
confidence: 72%
“…26 isotope concentration variations at 115 m and 125 m, the profiles of 3He and 4He are typical of what would occur in a lake where in situ 3H decays to increase the 3He concentration below the surface. (Torgersen et al (1977) discuss this situation in detail with samples from the Great Lakes of North America.) This excess 3He can be used to calculate a 3H_ 3 He water mass age according to the equation (Torgersen et al 1977):…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation